Feature Extraction Techniques in Keystroke Dynamics for Securing Personal Devices - Krishnaraj, N (International Journal of Computer Sciences and Engineering, 2015)
This paper presents a novel approach used to identify and analyze the features of keystroke dynamics. Keystroke dynamics is a authentication technique which aims to identify the person based on the behavioral characteristic (Typing Rhythms). The keystroke data like Duration, latency and digraph are measured using statistical techniques. The user keystroke patterns are collected and further it is analyzed to identify the quality features that will be given to feature subset selection for selecting the dominant features. The extracted features will be given to the feature subset selection for identifying dominant features.